Tourism Trends and Analysis: Insights from Nepal Tourism Statistics 2021 - Laxmi Kanta Sharma; Paudel, Vishal (Journal of Development and Administrative Studies, 2021)
Tourism is a cornerstone of Nepal’s economy, contributing significantly to GDP and employment. This study investigates tourism trends from 1995 to 2021, focusing on tourist arrivals, demographics, and economic impacts using data from the "Nepal Tourism Statistics 2021" report. The study reveals a peak in tourist arrivals at 1.2 million in 2019, followed by a severe decline due to the COVID-19 pandemic, which saw arrivals drop to 230,000 in 2020 and 150,000 in 2021. Despite this downturn, there was an increase in the average length of stay, indicating a shift in travel behavior. The research also documents a decrease in holiday visits, trekking, and pilgrimage activities during the pandemic, while noting a relative increase in tourism-related enterprises. The findings highlight the need for sustainable tourism strategies and investments in infrastructure to revitalize the sector and support economic recovery. This study provides valuable insights for policymakers and industry stakeholders to navigate post-pandemic challenges and foster long-term growth in Nepal’s tourism sector.